Pengaruh Terapi Generalis Terhadap Penurunan Tanda Dan Gejala Klien Halusinasi Pendengaran Di Ruang Rawat Inap Elang, Perkutut, Dan Merak: The Effect of Generalist Therapy on the Decrease of Clients Signs and Symptoms Hearing Hallucinations in the Inpatient Room Eagle, Turtle, and Peacock - restyan, rico (Dohara POAJ, 2022)
Introduction: The application of generalist therapy to the reduction of signs and symptoms of clients with auditory hallucinations in the inpatient room has a good impact on clients in controlling their hallucinations when they relapse. Methods: This study used a quasi-experimental design using a pre-posttest non-control group approach with hallucination nursing care interventions. The total sample used was 30 respondents who met the criteria with auditory hallucinations. All respondents were given generalist therapy from sessions 1-4 which were divided into 2 groups in the inpatient room Eagle, Turtle, and Peacock at Soeharto Heerdjan Mental Hospital Jakarta. Then the data is processed using a Paired Sample T-test. Results: The results of the study obtained that the mean value before being given generalist therapy was 43,30 and the mean value after being given generalist therapy was 24,60. There was a decrease in the mean value to 18,7. The results of statistical tests using the Paired Sample T-Test test obtained a p-value (0,000) <0,05. Discussion: There is a difference in the decrease in signs and symptoms of clients with auditory hallucinations before and after being given generalist therapy in the Eagle, Turtle, and Peacock inpatients at Soeharto Heerdjan Mental Hospital.